Antifungal susceptibility of 175 Aspergillus isolates from various clinical and environmental sources - Sabino, Raquel (2016)
Some environmental Aspergillus spp. isolates have been described as resistant to antifungals, potentially causing an emerging medical problem. In the present work, the antifungal susceptibility profile of 41 clinical and 134 environmental isolates of Aspergillus was determined using the CLSI microdilution method. The aim of this study was to compare environmental and clinical isolates with respect to their susceptibility, and assess the potential implications for therapy of isolates encountered in different environments. To our knowledge, this is the first report comparing antifungal susceptibility profiles of Aspergillus collected from different environmental sources (poultries, swineries, beach sand, and hospital environment). Significant differences were found in the distribution of the different species sections for the different sources. Significant differences were also found in the susceptibility profile of the different Aspergillus sections recovered from the various sources. Clear differences were found between the susceptibility of clinical and environmental isolates for caspofungin, amphotericin B and posaconazole, with clinical isolates showing overall greater susceptibility, except for caspofungin. In comparison to clinical isolates, hospital environmental isolates showed significantly less susceptibility to amphotericin B and posaconazole. These data indicate that species section identity and the site from which the isolate was recovered influence the antifungal susceptibility profile, which may affect initial antifungal choices.